Physicochemical quality and antioxidant changes in ‘Leb Mue Nang’ banana fruit during ripening - Youryon, Pannipa; Supapvanich, Suriyan (Agriculture and Natural Resources, 2017)
The physicochemical and antioxidant changes of ‘Kluai Leb Mue Nang’ banana fruit (Musa AA group) were investigated during ripening. The visual appearance, peel and pulp color, firmness, total soluble solids concentration (TSS), total acidity (TA) and bioactive compounds of the fruit at three stages of ripening (mature green, ripe and overripe) were monitored. Changes in both the peel and pulp color, texture, TSS and TA contents during banana ripening were similar to those of other banana fruits. Interestingly, the highest total antioxidants capacity and total phenols concentration were found in the ripe banana fruit. 2,2-Diphenyl-1-picrylhydrazyl radical scavenging activity remained constant and the highest total flavonoids concentration was found in the mature green fruit.